Prevalence and predictors of psychological assistance services for older individuals in Turkish society - Coşkun, Hüseyin; Yildiz, Ibrahim; Alkan, Ömer (Frontiers in Public Health, 2023)
Background/aim: Due to the high contribution of psychological problems to the decline in the comfortable lifestyle of the elderly, determining the factors that affect individuals’ receiving psychological services and searching for solutions based on these factors is one of the primary concerns of national and international decision-makers. This study aimed to identify the factors that affect elderly individuals’ access to psychological assistance services in Turkey. Methods: In this study, the Turkish Health Research micro dataset, which was conducted by the Turkish Statistical Institute (TURKSTAT) in 2016 and 2019, was employed. In this dataset, the data of 7,252 elderly individuals were analyzed. Using binary logistic analysis, the factors that are effective for obtaining psychological assistance for the elderly were identified. Results: According to the results of the analysis, factors such as gender, education, general health status, disease status, payment of health expenditures, and body mass index affected elderly individuals who received psychological assistance. Conclusion: In recent years, there has been a rise in the availability of psychological assistance services for the elderly. By identifying factors that increase the likelihood of receiving psychological assistance services, this study is expected to contribute to the creation and regulation of psychological assistance services to prevent possible psychological problems that may occur in old age, minimize the problems experienced by individuals, and promote a more comfortable lifestyle.